2008
DOI: 10.1163/156853508x360000
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Restoration as Public Spiritual Practice

Abstract: Th e practice of ecological restoration is the attempt to repair ecosystems that have been damaged or degraded, most often by past human activities. Restoration includes everything from removing dams to planting native trees, grasses and wildfl owers to bio-reactivating soil to controlling invasive plants to recontouring land. Beyond this, ecological restoration is the attempt to restore humans' relationship with nature. In the actual activities of restoring land, humans are in important ways restored to land.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Our analysis of the entwinement of different values, ethics, and pragmatics in the identified narratives of justification suggests that restoration professionals have done just that and that the boundary between the natural and the artificial is becoming increasingly blurred. This is in line with a number of authors who have argued ecological restoration has the potential to overcome the nature‐culture divide that has been pervasive in Western thought (Gobster ; Van Wieren ; Egan et al ; Hourdequin & Havlick ). These authors have suggested that this divide, and the way it has separated humans from nature, has resulted in a reliance on science and technology as the main instruments for development and progress.…”
Section: Reflectionssupporting
confidence: 87%
See 1 more Smart Citation
“…Our analysis of the entwinement of different values, ethics, and pragmatics in the identified narratives of justification suggests that restoration professionals have done just that and that the boundary between the natural and the artificial is becoming increasingly blurred. This is in line with a number of authors who have argued ecological restoration has the potential to overcome the nature‐culture divide that has been pervasive in Western thought (Gobster ; Van Wieren ; Egan et al ; Hourdequin & Havlick ). These authors have suggested that this divide, and the way it has separated humans from nature, has resulted in a reliance on science and technology as the main instruments for development and progress.…”
Section: Reflectionssupporting
confidence: 87%
“…Some authors (e.g. Van Wieren ; Hourdequin & Havlick ) furthermore view ecological restoration as a symbolic and redemptive practice aiming at restoring the distorted relationship between human and nature. Also for the question of what to restore , debate is ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first restoration initiatives began in the 1930s, these claims have been made, and continue to be made today (Martin, 2017). Recently, it has been claimed that handson ecological restoration can play a role in enabling societies to resolve environmental crisis, by governmental and nongovernmental organizations (e.g., Keenleyside, Dudley, Cairns, Hall, & Stolton, 2012;McDonald, Gann, & Dixon, 2016;Parks Canada, 2011) and scholars from a wide variety of disciplines (DiEnno & Thompson, 2013;Higgs, 2003;Jordan, 2003;Light, 2000;Miller, 2005;Pyle, 2003;van Wieren, 2008;White, 2012;Zylstra et al, 2014). Usually, defined as "the process of assisting the recovery of an ecosystem that has been degraded, damaged or destroyed" (Society for Ecological Restoration International, 2004, p. 3), ecological restoration has long been understood as an opportunity to bring together people and nature.…”
Section: Methodsmentioning
confidence: 99%
“…Working under the rubric of “lived religion,” the early years of this century saw a more systematic analysis of the religiosity of ecological and outdoor recreational practices. Close examinations of the homesteading movement, of restoration ecology, of surfing, and of fly‐fishing exemplify this trend (Gould ; Van Wieren ; Taylor 2007b; Sanford ; Snyder ).…”
Section: Theoretical Functionalismmentioning
confidence: 97%